An integrated solar energy, wastewater treatment and desalination plant for hydrogen and freshwater production - Demir, Murat Emre; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In this paper, a cost analysis study is undertaken for a commercial-scale hydrogen production and wastewater treatment plant, aiming to produce 1000 kg of hydrogen and treat 222 m(3) of wastewater per day. The present cost-analysis model considers the technological and economic implications of central and forecourt hydrogen generation technologies. The model employs a photoelectrochemical solar concentrator system with heliostats/concentrators to concentrate solar irradiation at a 10:1 intensity ratio onto multi junction photovoltaic/photoelectrochemical cell receivers submerged in an electrolyte reservoir and pressured to 20.7 bar. The photovoltaic cells are connected electrically to an electrolyte reserve and treat wastewater on the anode side using Fenton-like processes while generating H-2 on the cathode side. Then, the chemical oxygen demand-free wastewater is delivered to the electrodialysis plant for desalination, acid and alkaline production purposes. The concentrated light driven photoelectrochemical H-2 generation facility with a design capacity of 1,053 kg/day is used in the scale-up analyses. The cost of hydrogen is calculated to be $5.25/kg, excluding the profits obtained from the acid, alkaline and freshwater production. The yearly benefit from wastewater treatment is estimated as $81,030, respectively.
Keywords: Cost analysis; Hydrogen production; Desalination; Photovoltaics; Solar energy; Waste water treatment; ELECTRO-FENTON; ELECTRODIALYSIS; MEMBRANES; PEROXIDE; Thermodynamics; Energy & Fuels; Mechanics